From towncrier to radio: Exploring the growth of newscasting in Igbo language (Namibian Journal of Linguistics, Literature and Communication Studies, 2025)
The growth of urban cities in Igbo land, Nigeria has necessitated the use of radio to broadcast news to a larger Igbo speaking audience, hence Igbo radio newscasting has been normalised over from the traditional town criers in the Igbo local communities. Against this background, this study examines the growth of Igbo radio newscasting and some of the issues facing Igbo newscasters during news broadcast in the Igbo language.  Data were drawn from interviews collected from both retired and current Igbo newscaster veterans, and also through personal observations by the author. Findings show that time allocated to Igbo radio newscasting and stations that broadcasting in Igbo language has increased overtime. While the study argues that Igbo radio news has been on the growth from the time it started, it also pointed out areas where Igbo newscasters needs to improvements, and intervention especially in the area of curriculum development that is peculiar to the language.
Keywords: Igbo newscasting; Igbo Radio; Issues in Igbo Newscasting